Wild Woman a footnote, the desert, and my quest for an elusive saint. - Frykholm, Amy. (Minneapolis, Minnesota : Broadleaf Books, 2021)
In the dusty corner of a library, journalist Amy Frykholm discovers a footnote that leads her on a decades-long search for Mary of Egypt--runaway, prostitute, holy desert dweller, saint, and archetypal wild woman. As their storylines crisscross maps and centuries, the saint and the author meet at various thresholds, and both become more fully revealed as they enter the desert wild and wildly--in the embrace of the sacred.
Cover Page -- Copyright Page -- Contents -- Preface: Footnote to History -- Part I: Egypt -- Bring the Live Heart -- Find the Root -- Climb to the High Place -- Sift through the Sand -- Part II: Israel -- Be Astonished -- Cross the Threshold -- Open the Door -- Part III: Palestine and Jordan -- Get Lost -- Go into the Deeper Desert -- Melt -- Be Wild -- Epilogue: Translated -- Acknowledgments -- Appendices -- Glossary of People, Places, and Terms -- Life of Mary of Egypt: A Translation by Thomas F. Johnson and Amy Frykholm -- Life of Mary of Egypt: A Version in Poetry by Amy Frykholm -- Notes
Description based upon print version of record.
For Further Reading.
JSTOR
Keywords: Mary, -- of Egypt, Saint; Mary, -- of Egypt, Saint; Wilderness (Theology); Christian saints -- Egypt -- Biography; Women mystics -- Biography; Christian pilgrims and pilgrimages; Désert (Théologie); Femmes mystiques -- Biographies; Women mystics; Christian saints; Christian pilgrims and pilgrimages; Wilderness (Theology); Egypt; Biographies; Biographies; Biographies